Hands-on Industrial Internet of Things : create a powerful Industrial IoT infrastructure using Industry 4.0 /: create a powerful Industrial IoT infrastructure using Industry 4.0. (2018) - Veneri, Giacomo; Capasso, Antonio
No abstract available